Professional biofilm management during supportive periodontal therapy—a longitudinal observational study - Miriam Cyris; Georgina Hach; Christof E. Dörfer; Karim Fawzy El-Sayed; Christian Graetz (BMC Oral Health)
Abstract Background Professional mechanical biofilm reduction represents the cornerstone measure during supportive periodontal therapy (SPT). Conventionally, rotating polishing rubber cups (RCs) and brushes with polishing paste or air-polishing (AP) devices using low-abrasive powders can be used. This study aimed to evaluate the effectiveness of both methods in periodontitis patients in a university SPT setting. Methods Patients diagnosed with periodontitis who attended regular SPT at the Department of Conservative Dentistry and Periodontology at the University Hospital Schleswig-Holstein, Kiel campus, at least once a year between 2018 and 2023 were included. Clinical parameters such as number of teeth and pocket probing depth (PPD) were recorded at T1 (first documented SPT session) and T2 (last documented SPT session). Results A total of 430 patients (AP/RC: n = 152/n = 278) with an average age of 60.7(11.5) years, were included. Most patients had Stage III (AP/RC: 56.6%/56.8%) and Grade B (AP/RC: 52%/64.4%) periodontitis. The treatment time was 77.9(21.0) min and did not differ between groups (p = 0.378). No significant differences were found in the number of sites with PPD ≤ 4 mm at T1 or T2 (p > 0.05). Sites with PPD ≥ 5 mm differed significantly at T1 (AP: 8 [4–16], RC: 6 [3–12]; p = 0.002) but not at T2 (AP: 6 [3–13], RC: 5.5 [3–11]; p = 0.104). No significant intergroup differences were notable regarding stability, improvement, or deterioration of sites with PPD ≥ 5 mm over time. However, the AP group had significantly more multirooted teeth with Stage III furcation involvement regardless of bleeding on probing (BOP) at T1 (AP: 2 [1–5], RC: 1 [1–3]; p = 0.046) but not at T2. AP demonstrated a significant advantage in preventing deterioration of PPD ≥ 5 mm in molars (AP: 48 [45.3%], RC: 62 [33.3%]; p = 0.027). Conclusions Both methods of professional biofilm removal are similarly effective in terms of stabilizing or improving periodontal sites with PPD ≥ 5 mm when performed regularly. However, in molars with furcation involvement, RC intervention showed more favorable outcomes compared to AP, particularly in preventing the deterioration of sites with PPD ≥ 5 mm, in this study cohort treated in a specialized university-based SPT setting. Trial registration The study was retrospectively registered in the DRKS—German Clinical Trials Register ( https://www.drks.de ) with the registration-ID DRKS00037021 (22/05/2025).